Increased expression of fatty acid binding protein 4 in preeclamptic Placenta and its relevance to preeclampsia. (March 2016) - Yan, Yuying; Peng, Huilian; Wang, Peng; Wang, Hanzhi; Dong, Minyue
Abstract: The aim of this investigation was to determine the expression of fatty acid binding protein 4 (FABP4) in the placenta from women with preeclampsia and normal pregnancy, and to delineate the regulatory effects on thophoblast cell by FABP4. We determined the expression of FABP4 by real-time polymerase chain reaction (PCR) for messenger ribonucleic acid (mRNA) or enzyme-linked immunesorbent assay (ELISA) and Western blotting for protein. Small interference of ribonucleic acid (siRNA) and specific FABP4 inhibitor were used to inhibit FABP4. The proliferation, migration and invasion of trophoblastic cells (Swan-71 and Jar) were evaluated with cell counting kit-8, wound-healing test and transwell analysis respectively. We found the expression of FABP4 was significantly higher in the placenta of preeclamptic women than that of women with normal pregnancy (t = 4.244, P < 0.001 for mRNA; t = 4.536, P < 0.001 for protein). FABP4 siRNA significantly reduced the proliferation of trophoblasts (P < 0.001). The specific inhibition of FABP4 inhibited the proliferation of trophoblasts in a dose-dependent manner (P < 0.001) and the inhibitory effect increased as the concentration of inhibitor increased. FABP4 siRNA and specific inhibitor significantly decreased the migration (P < 0.001) and invasion (P < 0.001) of trophoblasts. We concluded the increase in placental FABP4 expression in preeclampsia may affect the function of trophoblast, and this increase may have a role in the pathogenesis of preeclampsia. Highlights: The expression of FABP4 was significantly increased in preeclamptic placenta. FABP4 siRNA significantly inhibited the proliferation, migration and invasiveness of trophoblast. Specific inhibition of FABP4 significantly reduced the proliferation, migration and invasiveness of trophoblast.